Cytochemical characterization of the endomembranous system during the oocyte primary growth in Serrasalmus spilopleura (Teleostei, Characiformes, Characidae) - Guimaraes, ACD; Quagio-Grassiotto, I (Churchill Livingstone, 2005)
The morphophysiological changes that occur during oocyte primary growth in Serrasalmus spilopleura were studied using ultrastructural cytochemical techniques. In the previtellogenic oocytes endoplasmic reticulum components, Golgi complex cisternae and vesicles, lysosomes, multivesicular bodies and some electron-dense vesicles react to acid phosphatase (AcPase) detection. The endoplasmic reticulum components, Golgi complex cisternae and vesicles also react to osmium tetroxide and potassium iodide impregnation (KI). These structures, except for the Golgi complex cisternae, are strongly contrasted by osmium tetroxide and zinc iodide impregnation (ZIO). Some electron-dense vesicles are ZIO-stained, while microvesicles in the multivesicular bodies and other large isolated cytoplasmic vesicles are contrasted by KI. At primary oocyte growth, the activity of the endomembranous system and the proliferation of membranous organelles are intense. The biosynthetic pathway of the lysosomal proteins such as acid phosphatase, involves the endoplasmic reticulum, Golgi complex, vesicles with inactive hydrolytic enzymes and, finally, the lysosomes. The oocyte endomembranous system have reduction capacity and are involved in the metabolism of rich in SH groups. (c) 2005 Published by Elsevier Ltd.
Keywords: ultrastructural cytochemistry; acid phosphatase; oocyte; Serrasalmus spilopleura